ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESEJAHTERAAN MASYARAKAT KOTA PADANG - Rizki Afri Mulia; Nika Saputra (Jurnal EL-RIYASAH, 2020)
This study aims to analyze the factors that affect the welfare of the people of the City of Padang measured using the Human Development Index consisting of: 1) To determine the effect of the Per Capita Gross Regional Domestic Product on the welfare of the people in the City of Padang. 2) To determine the effect of number of Poor in community welfare in Padang. 3) To determine the effect of Unemployment Rate on the welfare of people in the city of Padang. The research method used in this research is descriptive quantitative research method. The sampling technique in this study is total sampling. Data collection was performed using documentation and hypothesis testing techniques in this study using multiple linear regression test. Based on the results of the study note that: 1) The regression coefficient value of GDP per capita is equal to 0.0000002 with a probability of 0.001 which is smaller than 0.05. 2) The regression coefficient value of the number of poor population is 0.156 with a probability of 0.526 which is smaller than 0.05. 3) The regression coefficient value of the Open Unemployment Rate is -0,00014 with a probability of 0.117 less than 0.05. The conclusions that can be drawn are as follows: 1) Gross Regional Domestic Product (GRDP) has a positive and significant effect on the welfare of the people in Padang City. 2) The number of poor people has no significant effect on the welfare of the people in the city of Padang. 3) Open Unemployment Rate has no negative and significant effect on the welfare of the people in Padang City.